1998
DOI: 10.1164/ajrccm.158.1.9712001
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Worsening of Tuberculosis Following Antiretroviral Therapy in Patients with AIDS

Abstract: Transient worsening of tuberculous symptomatology and lesions following antituberculous therapy (paradoxical response) has previously been described as a rare occurrence. To determine the incidence of paradoxical responses in patients with AIDS and TB who are treated with antituberculous therapy and subsequently with combination antiretroviral therapy (ARV), we conducted a prospective study of 33 HIV-seropositive TB patients treated with anti-TB therapy and antiretroviral therapy (Group 1) compared with 55 HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
330
2
37

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(386 citation statements)
references
References 15 publications
17
330
2
37
Order By: Relevance
“…This might be due to partial recovery of anti-HHV-8 immune function, probable infection by wild-type HIV strains and a presumed better adherence compared to previously HAART-treated patients. Nevertheless, paradoxical transient deterioration have been described in KS patients, as seen in patients with tuberculosis and other opportunistic infections (Narita et al, 1998;Baril et al, 2000;Stone et al, 2002). Shelburne et al (2005) showed that patients who have been antiretroviral naive at time of diagnosis of their opportunistic infection have an increased risk of immune inflammatory syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to partial recovery of anti-HHV-8 immune function, probable infection by wild-type HIV strains and a presumed better adherence compared to previously HAART-treated patients. Nevertheless, paradoxical transient deterioration have been described in KS patients, as seen in patients with tuberculosis and other opportunistic infections (Narita et al, 1998;Baril et al, 2000;Stone et al, 2002). Shelburne et al (2005) showed that patients who have been antiretroviral naive at time of diagnosis of their opportunistic infection have an increased risk of immune inflammatory syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…KUMARASAMY et al 9 published an incidence of 15.2 cases/100 patients/year to IRIS related with tuberculosis. NARITA et al 14 published a prevalence of 36% for Mycobacterium tuberculosisassociated IRIS.…”
Section: Discussionmentioning
confidence: 99%
“…Narita et al informaron la reacción paradójica a la iniciación del tratamiento antituberculoso en 12 (36%) de 33 pacientes positivos para VIH que concomitantemente iniciaron HAART, en 2 (7%) de 28 pacientes positivos para VIH tratados para tuberculosis antes del advenimiento de la HAART y en 1 (2%) de 55 pacientes negativos para VIH que comenzaron quimioterapia tuberculostática (28).…”
Section: Discussionunclassified